THEORETICAL BASIS OF TEACHING PRIMARY CLASS STUDENTS TO THINK INDEPENDENTLY IN PROBLEM EDUCATION TOOLS (E Conference Zone, 2022)
This article shows ways to widely use problem-based educational tools in teaching primary school students to think independently, highlights the importance and advantages of modern pedagogical technologies.